Identifikasi Penguasaan Mahasiswa tentang Kompetensi Pedagogik Guru Bimbingan dan Konseling - Novela Hayati; Friscilla Wulan Tersta; Freddi Sarman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Guidance and Counseling (BK) students have a strategic role as prospective BK teachers who will carry out important tasks in the world of education. As prospective BK teachers, they are required to master four competencies based on the Regulation of the Minister of National Education Number 27 of 2008, especially pedagogical competencies. Pedagogical competence is the ability that teachers must have to manage the learning process effectively. Through PLP, students are expected to be able to apply pedagogical theory to real BK service practices. This research is needed to determine the level of mastery of pedagogical competencies possessed by Guidance and Counseling students, FKIP, Jambi University in the aspects of educational theory, educational practice, counselee behavior, and the essence of BK services. This type of research uses a descriptive quantitative approach. Descriptive quantitative research aims to collect and analyze numerical data to describe conditions on the ground as they exist.